Tic At The Regulations for the High Education Syllabus in Colombia - Mesa Jiménez, Fredy Yesid; Forero Romero, Aracely (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article presents a revision about the regulations’ formulation and evolution related to information and communication technology (TIC) in the processes of standards registration and high quality accreditation, and in the Colombian higher education’s syllabus and its implementation at Univesidad Nacional de Colombia (UNAL) and Universidad Pedagógica y Tecnológica de Colombia (UPTC). The qualitative analysis was demarcated in the education’s historical line with an approach on the comparative education. Principal and secondary documentary sources were examined. The TIC’s mandatory valuation was emphasized on indicators associated to TIC infrastructure in spite of rules investigate about capacitation and use of these technologies, in which a systematic monitoring must be boosted. The regulations must give emphasis to pedagogical appropriation from teachers, it would drive actions and strategies at the interior of the universities, moreover, it would expound procedures to get the curricular, pedagogical and institutional strategies integrated in order to assure its use and achieve the planned benefits of technology for education.